ANALISIS DAMPAK RANGKAP JABATAN TERHADAP EFEKTIVITAS KERJA DI PT. YYY. - Alfiana Marfuatus Sholichah; Roziana Ainul Hidayati (Journal of Management and Creative Business, 2023)
The purpose of this research is to analyze the Effectiveness of Multiple Positions at PT. YYY. In this study, the author's method was to employ descriptive qualitative techniques. Interviews are the technique used to collect data. Three informants were selected by the researcher as part of the sample for interview. According to researchers' observations, the effectiveness of employee work has not been maximized because there are still tasks that cannot be completed on time due to duplicates, necessitating the sacrifice of one of these tasks.